The cellular microbiology of Salmonellae interactions with macrophages. (23rd October 2019) - Petersen, Erik; Miller, Samuel I.
Abstract: Salmonellae are important enteric pathogens that cause gastroenteritis and systemic illnesses. Macrophages are important components of both the innate and acquired immune system, acting as phagocytes with significant antimicrobial killing activities that present antigen to the adaptive immune system. Macrophages can also be cultured from a variety of sites as primary cells, and the study of the survival and interactions of Salmonellae with these cells is a very early model of infection and cellular microbiology. This review traces the history of discoveries made using Salmonellae infection of macrophages and addresses the possibility of future research in this area, in particular with regards to understanding the complexity of individual bacteria and macrophage cell variability and how such heterogeneity may alter the outcome of infection.